Neutron measurements from antineutrino hydrocarbon reactions - Elkins, M (2019)
This document was prepared by members of the MINERvA Collaboration using the resources of the Fermi National Accelerator Laboratory, a U.S. Department of Energy, Office of Science, HEP User Facility. Fermilab is managed by Fermi Research Alliance, LLC (FRA), acting under Contract No. DE-AC02-07CH11359. These resources included support for the MINERvA construction project, and support for construction also was granted by the United States National Science Foundation under Grant No. PHY-0619727 and by the University of Rochester. Support for scientists for this specific publication was granted by the United States National Science Foundation under Grants No. PHY-1306944 and No. PHY-1607381. We are grateful for the United States National Science Foundation's decade of direct support to the Soudan Underground Lab outreach program, including Grant No. PHY-1212342; this analysis originated as the research component for two summer undergraduate outreach interns. Support for participating scientists was provided by NSF and DOE (USA) by CAPES and CNPq (Brazil), by CoNaCyT (Mexico), by Proyecto Basal FB 0821, CONICYT PIA ACT1413, Fondecyt 3170845 and 11130133 (Chile), by CONCYTEC (Consejo Nacional de Ciencia, Tecnologia e Innovacion Tecnologica), DGI-PUCP (Direccion de Gestion de la Investigacion-Pontificia Universidad Catolica del Peru), and VRI-UNI (Vice-Rectorate for Research of National University of Engineering) (Peru); by the Latin American Center for Physics (CLAF); and NCN Opus Grant No. 2016/21/B/ST2/01092 (Poland). We thank the MINOS Collaboration for use of its near detector data. Finally, we thank the staff of Fermilab for support of the beamline, the detector, and the computing infrastructure.